2010
DOI: 10.1038/onc.2010.246
|View full text |Cite
|
Sign up to set email alerts
|

The E2F5 repressor is an activator of E6/E7 transcription and of the S-phase entry in HPV18-associated cells

Abstract: High-risk papillomavirus type 18 (HPV18) is one of the less represented HPV types in low-grade lesions of the anogenital tract, whereas it occupies the second place in cervical cancer, where it can be found in 16% of the cases worldwide, after HPV16 present in 54% of them. These epidemiological data indicate that HPV18 infection is more prone to carcinogenic progression. The main oncogenic proteins, E6 and E7 of HPV18, are functionally comparable to the homologous proteins of the other highrisk viruses, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
11
1
1
Order By: Relevance
“…Recently, it has been shown that E2F5 positively regulates S‐phase entry in HeLa cells and that this activation of the cell cycle is specific for HPV18‐expressing cells. This suggested that HPV18 could act changing the role of E2F5 from being a cell‐cycle repressor to an activator, thus contributing to the higher oncogenic potential of HPV18 respect to other high‐risk HPV types (Teissier et al, 2010).…”
Section: Prb and E2f Family In Cancermentioning
confidence: 99%
“…Recently, it has been shown that E2F5 positively regulates S‐phase entry in HeLa cells and that this activation of the cell cycle is specific for HPV18‐expressing cells. This suggested that HPV18 could act changing the role of E2F5 from being a cell‐cycle repressor to an activator, thus contributing to the higher oncogenic potential of HPV18 respect to other high‐risk HPV types (Teissier et al, 2010).…”
Section: Prb and E2f Family In Cancermentioning
confidence: 99%
“…The impact of the S-phase environment on the viral life cycle is not restricted to lytic viral replication but is also involved in the episomal genome maintenance during viral latency or reactivation processes, as was recently shown for EBV and the Kaposi’s Sarcoma-associated herpesvirus (KSHV) [34], [35]. Strikingly, infections with oncogenic viruses (e.g., SV40, HPV, HTLV-1, EBV) are often associated with S-phase deregulation and genomic instability, preferentially occurring during this critical phase of the cell cycle [24], [27], [33], [36].…”
Section: Introductionmentioning
confidence: 99%
“…The E6 and E7 oncoproteins have been shown to be key mediators of the development of HPV-induced cervical carcinoma. HPV-related transcription factors are involved in the G1/S and G2/M transition within the cell cycle (9). The E6 protein, which associates with E6-associated protein (E6AP), induces p53 degradation…”
Section: Introductionmentioning
confidence: 99%